PENGARUH FUNGI MIKORIZA ARBUSKULA DAN PEMUPUKAN N,P,K SPESIFIK LOKASI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG PADA TANAH GAMBUT - Ashari -; Mulyadi Safwan; Dwi Zulfita (Fakultas Pertanian Universitas Tanjungpura, 2013)
This study aims to determine the best dose of fertilizer N, P, K for the growth and yield of corn plant which inoculated and non-inoculated with Arbuscular Mycorrhiza Fungi (AMF). This research was conducted at the experimental farm of the Faculty of Agriculture Tanjungpura University, Pontianak and begining on November 2011 to March 2012. The experimental units were arranged in a Completely Random Design (CRD) factorial with 2 factor of treatment and 3 replications : (1). AMF inoculation (M) : m0 = with inoculation of AMF ;m1 = without inoculation of AMF and (2). site-specific fertilizer recommendations corn plants in peat soil at Sungai Raya district (P): p 0 = no fertilizer N, P, K, p1 = 25% of fertilizer N, P, K, p2 = 50% of fertilizer N, P, K, p3 = 75% of fertilizer N, P, K, p4 = 100% fertilizer N, P, K. Each combination treatment plant consists of 3 samples. The variables observed in this study is the chlorophyll content of leaves, plant dry weight, uptake of N, P, K, the percentage of infected roots, shelled dry weight per plant, number of seeds on row and cob diameter, and environmental monitoring. The result showed that addition AMF and fertilizer N, P, K influenced for root infection, uptake of P and K, plant height, leaf area, and plant dry weight. Keywords: AMF, NPK, Corn plant, Peat Soil